Chapter 10 Breathlessness From Bodily Symptom to Existential Experience - Williams, Tina (Rowman & Littlefield International, 2018)
This chapter uses a phenomenological approach to investigate the philosophical significance of a common yet debilitating experience: the experience of severe and pathological breathlessness. Using two key examples of breathlessness in the case of respiratory disease (somatic) and in anxiety disorders (considered as mental disorder) we show why a phenomenological approach to the study of these experiences is needed and how the distinction between the somatic and the mental comes under pressure when considering a complex phenomenon like breathlessness.